The Cosmic Dance of Lord Shiva: Divulgence of Vedic Cosmogony and Culture in Shiva TandavaStotram - Bhandari, Sabindra Raj (The Outlook: Journal of English Studies, 2022)
This article intends to explore and interpret the Vedic concept of creationism in the Tandava of Lord Shiva and Shiva TandavaStotram with Ananda Coomaraswamy’s philosophy of cosmic dance. Shiva TandavaStotram is a collection of fourteen Sanskrit hymns that rejuvenate and systematize all the dynamics of Lord Shiva’s cosmic dance in a rhythmic way. This article further examines the multifaceted dimensions of Lord Shiva’s cosmic dance with Hindu cosmology and modern viewpoints of physics. The Tandava is the frantic, but divine dance of Lord Shiva with ecstasy and bliss. All dualities and antagonism merge and become one in the perfect combination of frantic body movement and ecstatic rhythm of the mantras. In this regard of frantic as wild but natural and rhythmic as the beauty of creation, this is the cosmic dance to create, evolve, sustain, veil, and unveil the creation. Lord Shiva is Nataraja, the cosmic dancer who is both the destroyer and creator. He destroys to create. His cosmic dance is the dance of entire creations and universe, and the dance of atoms as per modern physics. It is the symbolic pattern of cosmology postulated in the Vedic philosophy with manifold transcendence of time and space and it has become the metaphor of creation in the modern world. Even in the secular context, the image of the cosmic dance of Lord Shiva gnashes the metaphorical value. For instance, the sculptor of Nataraja Shiva stands outside the European Organization of Nuclear Research (CERN) in Geneva, Switzerland. Shiva TandavaStotram exhibits all of these exposures of cosmic dance of Lord Shiva. This article implements the paradigm of qualitative research and textual analysis method using the theoretical tool developed by Coomaraswamy and supported by modern physics in order to explore and interpret these multifaceted aspects in Shiva TandavaStotram. In this sense, this paper becomes a threshold to enter the cultural and cosmological dimensions of the Tandava of Lord Shiva that prevail in the domain of Indian Philosophy.